Morphology and morphometry of mental foramen in adult human mandibles of North Indian population - Seema; Poonam Verma (Wolters Kluwer Medknow Publications, 2015)
Background and aim : Mental foramen is an oval or circular opening present on the anterior surface of mandible through which the mental nerve and vessels exit. It forms an important landmark for human mandible for both invasive and noninvasive procedures. Its position vary according to the age and race. The aim of the study is to provide data on morphology and morphometry of mental foramen. Materials and Methods : The present study was done on ninety dried adult human mandibles of unknown age and sex. Incidences and shapes of the mental and accessory mental foramen were observed. Size and the distances from the various landmarks were noted with the help of digital Vernier calipers. Results: Mental foramina were found bilaterally in all (100%) the mandibles. Accessory mental foramina were found in five mandibles (5.5%) on right side and three mandibles (3.3%) on left side. Shape of the mental foramina was predominantly rounded. Average size of mental and accessory mental foramina was 2.56 mm and 1mm respectively. The position of the mental foramina below the apex of second premolar , between the first and second premolar and between the second premolar and first molar and below the apex of first premolar tooth were 64.4%, 21.1%, 8.8% and 5.5% respectively. The average distance of the accessory mental foramina from the mental foramen was 0.66 mm and average location was below the first molar tooth. Conclusion: All these findings can supplement useful data for population diversities and can help the surgeons, anatomists, orthodontists and paleoanthropologists to carry out their procedures successfully.